2009
DOI: 10.1016/j.physrep.2008.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The Magnus expansion and some of its applications

Abstract: Approximate resolution of linear systems of differential equations with varying coefficients is a recurrent problem shared by a number of scientific and engineering areas, ranging from Quantum Mechanics to Control Theory. When formulated in operator or matrix form, the Magnus expansion furnishes an elegant setting to built up approximate exponential representations of the solution of the system. It provides a power series expansion for the corresponding exponent and is sometimes referred to as Time-Dependent E… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
1,300
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,091 publications
(1,372 citation statements)
references
References 217 publications
(534 reference statements)
10
1,300
0
3
Order By: Relevance
“…By rearranging this relation, we obtain a differential equation for U (s) whose formal solution is given by the path-or S-ordered exponential [86,87] …”
Section: General Conceptmentioning
confidence: 99%
“…By rearranging this relation, we obtain a differential equation for U (s) whose formal solution is given by the path-or S-ordered exponential [86,87] …”
Section: General Conceptmentioning
confidence: 99%
“…A simpler and more general method is proposed here to solve (3.17) based on the Magnus expansion (Magnus 1954;Blanes et al 2009). In this method, the solution of (3.17) is written as…”
Section: General Analytical Solutionmentioning
confidence: 99%
“…is satisfied (see Blanes et al (2009);Casas (2007); Moan & Niesen (2006) for more details), but may diverge for larger values of the integral. In the above, || · || 2 is the 2-norm of the matrix, which for a square matrix is equal to the spectral norm (the largest singular value of the matrix), and can be calculated as…”
Section: General Analytical Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, the coupling terms contributing to the decoherence errors undergo an effective renormalization. This renormalization transformation can be considered as the cancelation of the terms in the Magnus expansion of the effective Hamiltonian [26]. This analysis assumes ideal pulses having zero width, in which case it has been shown that DD sequences can be designed to make higher-order system-bath coupling terms vanish [4,22,27].…”
Section: Dynamical Decouplingmentioning
confidence: 99%